G-5555 synergized miR-485-5p to alleviate cisplatin resistance in ovarian cancer cells via Pi3k/Akt signaling pathway. (August 2020) - Qiao, Hai-feng; Liu, Ying-lei; You, Jun; Zheng, Yan-li; Chen, Li-ping; Lu, Xiao-Yan; Du, Lei; Shan, Feng; Liu, Man-hua
Highlights: This study focus on mechanism of miR-485-5p to find out functions of this microRNA in resistance of ovarian cancer. In drug resistant cancer cell line, miR-485-5p was expressed higher than tumor cell line. As the cisplatin concerntration increased, miR-485-5p decreased. miR-485-5p mimics induced lower cisplatin resistance while miR-485-5p inhibitor caused higher resistance. PAK1 targeted miR-485-5p and inhibited miR-485-5p. PAK1 inhibitor helped to lower the resistance to cisplatin caused by miR-485-5p upregulation. miR-485-5p mimics silenced Pi3k/Akt signaling and PAK1 inhibitor aggravated the silencing. Inhibition of Pi3k/Akt signaling increased miR-485-5p, thereby decreasing the cisplatin-resistance in OVCA433-CR. miR-485-5p decreased cisplatin resistance in ovarian cancer cells via Pi3k/Akt signaling, suggesting that miR-485-5p upregulation might alleviate the cisplatin resistance in ovarian patients. Abstract: The present study was meant for the discovery of the underlying functions of miR-485-5p in ovarian cancer concerning cisplatin resistance in vitro. RT-qPCR assessed the miR-485-5p expression in ovarian cancer cell lines, normal cells and cisplatin-resistant Cell line OVCA433-CR. After OVCA433-CR treated with 0, 3, 5umol/L cisplatin, miR-485-5p expressions were determined. MTT observed the cell cytotoxicity in OVCA433-CR after regulation of miR-485-5p. Targets can predicted the putative binding between miR-485-5p and PAK1 and Luciferase Assay verified this. RT-qPCR decided the inhibitory effect in between. MTT tested the cytotoxicity in different combinations of miR-485-5p and PAK1. Western Blot tested the phosphorylation of Pi3k and Akt in response to miR-485-5p and PAK1 interplay. We evaluated the role of Pi3k/Akt signaling in regulation of miR-485-5p and cisplatin resistance with Wortmannin. miR-485-5p was lower expressed in ovarian cancer cells than normal ones and even lower in OVCA433-CR than OVCA433. As the cisplatin concerntration increased, miR-485-5p decreased. miR-485-5p mimics induced lower cisplatin resistance while miR-485-5p inhibitor caused higher resistance. PAK1 targeted miR-485-5p and inhibited miR-485-5p. PAK1 inhibitor helped to lower the resistance to cisplatin caused by miR-485-5p upregulation. miR-485-5p mimics silenced Pi3k/Akt signaling and PAK1 inhibitor aggravated the silencing. Inhibition of Pi3k/Akt signaling increased miR-485-5p, thereby decreasing the cisplatin-resistance in OVCA433-CR. miR-485-5p decreased cisplatin resistance in ovarian cancer cells via Pi3k/Akt signaling, suggesting that miR-485-5p upregulation might alleviate the cisplatin resistance in ovarian patients.